If it is not healing, do worry about it! - Schade, Alexander Thomas (BMJ Publishing Group, 2013)
We present the case of a 44-year-old patient who crushed her ring finger in a door 4 months earlier. She was treated in the community for her chronic fingertip wound/pyogenic granuloma. As the lesion was not healing with regular wound management she was eventually referred to secondary care for an opinion. She underwent immediate excisional biopsy with safe margins for tissue diagnosis and had histological confirmation of an advanced malignant melanoma. The staging head, neck, thorax, abdomen and pelvic CT showed lymph node enlargement and widespread metastatic lesions. Our case shows how if hand lesions are not resolved following trauma, the patient needs to be assessed for unusual pathologies and, if necessary, or in doubt, referred to the specialists.